2020
DOI: 10.1111/spc3.12524
|View full text |Cite
|
Sign up to set email alerts
|

Power corrupts (or does it?): An examination of the boundary conditions of the antisocial effects of experienced power

Abstract: One of the most common conclusions in the power literature is that when people feel powerful, they behave in selfish and antisocial ways. While this conclusion tends to permeate the literature, research also recognizes that there are factors that can mitigate the corrupting nature of power, and that the experience of power may also lead to more positive and prosocial outcomes. In this article, we review findings that illustrate how individual differences, the contexts in which people experience power, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 92 publications
(165 reference statements)
1
19
1
Order By: Relevance
“…The second, perhaps most noteworthy, finding from this research is that the perception of having power is associated with greater destructive and lower constructive responses to the extent that the conflict was severe and participants had a low IOS. We provide evidence that powerful individuals do not invariably behave destructively in a conflictual situation instead, these findings advance the close relationship literature by identifying the particular conditions under destructive responses can be triggered in powerful individuals (Foulk et al, 2020). Specifically, as we have shown, these oppositional responses may be particularly relevant in situations of severe conflict, which presumably endanger their important personal goals (Carpenter, 2017).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The second, perhaps most noteworthy, finding from this research is that the perception of having power is associated with greater destructive and lower constructive responses to the extent that the conflict was severe and participants had a low IOS. We provide evidence that powerful individuals do not invariably behave destructively in a conflictual situation instead, these findings advance the close relationship literature by identifying the particular conditions under destructive responses can be triggered in powerful individuals (Foulk et al, 2020). Specifically, as we have shown, these oppositional responses may be particularly relevant in situations of severe conflict, which presumably endanger their important personal goals (Carpenter, 2017).…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, previous work has shown that when threats to power are high, restoring power has priority, leading to a cascade of defensive responses that aim at protecting individuals from harm (Bukowski et al, 2017;Deng et al, 2018;Weiss et al, 2020). Thus, we suggest that the higher the perceived degree of conflict, the more the power-holder sees reasons to suspect the possibility of their own goals could be blocked and thus, they might respond to perceived constraints upon their power by increasing negative or antisocial behaviors to get their way during interpersonal conflicts (Carpenter, 2017;Deng et al, 2018;Foulk et al, 2020). As a result of these dynamics, we predicted that the perception of having power would be associated with an increase in destructive responses during romantic conflicts (and a decrease in constructive ones), to the extent that people identify romantic conflict as severe.…”
Section: Untangling When Power Does Promote Destructive Responses In mentioning
confidence: 84%
See 2 more Smart Citations
“…Even though some empirical evidence backs up this observation (Bendahan et al, 2015;Giurge et al, 2019), evidence is inconsistent (see Fleischmann et al, 2019;Foulk et al, 2020), and research remains incomplete. In addition, evidence has focused mainly on the domain of gains (e.g., cheating for money and other resources).…”
Section: Introductionmentioning
confidence: 99%